2014
DOI: 10.1071/am13003
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of the ecology of the kalubu bandicoot (Echymipera kalubu) and observations on Raffray’s bandicoot (Peroryctes raffrayanus), Eastern Highlands Province, Papua New Guinea

Abstract: Abstract. Bandicoots in the family Peroryctidae in New Guinea are widespread and relatively abundant, but little is known of their ecology. We present the first detailed study on the ecology of the kalubu bandicoot (Echymipera kalubu) and observations on Raffray's bandicoot (Peroryctes raffrayanus), from mid-montane forest in Papua New Guinea. Both species were primarily nocturnal and utilised a range of habitats including those modified by human activity, although Raffray's bandicoot was more frequently encou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 17 publications
1
1
1
1
Order By: Relevance
“…Despite high attachment longevity overall, the frequency of rain and daily maximum temperature had a significant, negative effect on the TTND of tail-mounted ABDs. This supports findings by Moseby and O'Donnell (2003) where longevity was notably reduced in the summer months (late December to February) and by Hope (2012) and Cuthbert and Denny (2014) where rainfall and humidity reduced TTND. This is the first study, however, to indicate a statistically significant (P < 0.05) reduction in TTND due to environmental factors.…”
Section: Attachment Performancesupporting
confidence: 89%
See 1 more Smart Citation
“…Despite high attachment longevity overall, the frequency of rain and daily maximum temperature had a significant, negative effect on the TTND of tail-mounted ABDs. This supports findings by Moseby and O'Donnell (2003) where longevity was notably reduced in the summer months (late December to February) and by Hope (2012) and Cuthbert and Denny (2014) where rainfall and humidity reduced TTND. This is the first study, however, to indicate a statistically significant (P < 0.05) reduction in TTND due to environmental factors.…”
Section: Attachment Performancesupporting
confidence: 89%
“…heat and rain) or intrinsic (e.g. digging behaviour) factors (Moseby and O'Donnell 2003;Hope 2012;Cuthbert and Denny 2014), but a detailed analysis of the factors that may cause early detachment of tail-mounted ABDs has not yet been done.…”
Section: Introductionmentioning
confidence: 99%
“…The body length of bandicoot in this research was 23.97±3.48 cm, shorter than the findings by Maker et al (2016) which was at 38.2± 4.76 cm; and Warsono (2009) which was at 26.66±3.53 cm. Furthermore, the hind legs length of bandicoot in this research was 7.14±1.00 cm, longer than findings by Cuthbert and Denny (2014), which showed that the hind legs length of the bandicoot was 5.59±0.29 cm. The tail length in this study was 7.77±1.52 cm, relatively similar with the findings by Warsono (2009), which was at 7.89±1.30 cm; and Culberth and Denny (2014), which was at 7±0.7 cm.…”
Section: Body and Carcass Weight Of Male Bandicootcontrasting
confidence: 75%
“…; 22 Hogan et al. ; 23 West, ; 24 Poole, ; 25 Ashwell, ; 26 Voss & Jansa, ; 27 Gardner, ; 28 Patterson, ; 29 Soderquist, ; 30 Cuthbert & Denny, ; 31 Aplin et al. ; 32 Wood Jones, ; 33 Harris, ; 34 Collins, ; 35 Nowak, ; 36 Cooper et al.…”
Section: Methodsunclassified